Examining the Relationship between Emotional Intelligence and Learning Motivation in Islamic Moral Education - Ai Nurul Wardatul Suroya; Ulfah; Eliva Sukma Cipta; M Aditya Firdaus (Yayasan Sahabat Literasi Edukasi dan Publikasi Bandung, 2025)
Motivation is a crucial factor that helps students achieve educational success. Students with high learning motivation tend to be more enthusiastic and possess a strong drive to acquire knowledge. However, low learning motivation in the Akidah Akhlak subject remains a problem, which is presumed to be related to students’ emotional intelligence that has not yet developed optimally. Students with well-developed emotional intelligence are generally able to motivate themselves to stay focused on learning and actively participate in classroom activities. In reality, many students are still unable to motivate themselves effectively, as indicated by infrequent task completion, a tendency to give up easily when facing difficult assignments, low classroom participation, and mental disengagement during learning activities. This study aims to: (1) describe students’ emotional intelligence, (2) describe students’ learning motivation, and (3) examine the relationship between emotional intelligence and learning motivation. The study employed a quantitative approach using a survey method. The research population consisted of 81 tenth- and eleventh-grade students at SMK Addimyati Bandung, and the entire population was used as the research sample through total sampling. Data were collected using Likert-scale questionnaires adapted from the indicators of each variable and were analyzed using descriptive statistics and Pearson Product–Moment correlation analysis. The results indicate that students’ emotional intelligence and learning motivation are generally at a good level. Specifically, 64.2% of students were categorized as having moderate emotional intelligence, while 72.8% were categorized as having moderate learning motivation. The correlation analysis revealed a significant relationship between emotional intelligence and learning motivation.